Consumer behavior in clothing industry and its relationship with open innovation dynamics during the COVID-19 pandemic - Ardvin Kester S. Ong; Maria Arielle Cleofas; Yogi Tri Prasetyo; Thanatorn Chuenyindee; Michael Nayat Young; John Francis T. Diaz; Reny Nadlifatin; Perwira Redi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The fashion industry has been continuously growing over the years, yet it is an industry that was greatly affected by the COVID-19 pandemic. The purpose of the study was to determine the factors affecting buying behavior of Filipinos towards clothing apparel during the COVID-19 pandemic. There were 457 respondents who voluntarily participated and answered an online questionnaire. Structural equation modeling (SEM) indicated that marketing mix was found to have significant effects on attitude, subjective norm, and perceived behavioral control, which subsequently led to purchase intention. In addition, the COVID-19 latent variable was found to have significant effects on self-perceived severity and self-efficacy, which subsequently led to attitude and purchase intention. Interestingly, marketing mix was found to have the highest effect on actual purchase, which indicated that innovation dynamics are the keys for the buying behavior. The SEM construct can be applied to determine the clothing apparel buying behaviors of consumers in other countries, particularly during the COVID-19 pandemic. Finally, advertisements, promotions, sales, and health safety should be considered as innovation dynamics during the COVID-19 pandemic.
Keywords: 650; consumer behavior; COVID-19 pandemic; fashion industry; innovation dynamic; open innovation; protection motivation theory; theory of planned behavior